Implementation Of PSAK 71 Financial Instruments In The Banking Sector During The Covid-19 Pandemic - Arlie Irham Yusdika; Dyah Purwanti (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2021)
This study aims to analyze the impact of the COVID-19 pandemic on the application of PSAK 71 around financial instruments in the banking sector. The study uses a qualitative method with a literature study approach and content analysis. This study observes changes in the allowance for impairment losses (CKPN) balance from the fourth quarter of 2019 to the third quarter of 2020. The study shows a significant increase in the balance of allowance for impairment losses, which impacted the disclosure of earnings in the financial statements. Moreover, banks should reclassify credit risk status. However, government intervention limited this reclassification. It has implications for decreasing the reliability of presenting the financial statements' quality of information on instruments.